2022
DOI: 10.3390/v14112336
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 Seroprevalence among Canadian Blood Donors: The Advance of Omicron

Abstract: With the emergence of the SARS-CoV-2 Omicron variant in late 2021, Canadian public health case/contact testing was scaled back due to high infection rates with milder symptoms in a highly vaccinated population. We monitored the seroprevalence of SARS-CoV-2 nucleocapsid (anti-N) and spike protein (anti-S) antibodies in blood donors across Canada from September 2021 to June 2022 in 202,123 randomly selected samples. Multivariable logistic regression of anti-N positivity with month, age, sex, racialization, regio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 53 publications
(85 reference statements)
0
9
0
Order By: Relevance
“…There are a limited number of publications exploring seroprevalence against SARS-CoV-2 after the Omicron BA.1 wave. However, the published studies examining the general population or specific groups, e.g., blood donors or children, uniformly showed a high increase in infection-induced antibodies [ 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 ]. The wide spread of infections and gradual rise in vaccination coverage in the period covered in this study, although at a slower pace than in 2021, resulted in a high proportion of people with positive SARS-CoV-2 antibodies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are a limited number of publications exploring seroprevalence against SARS-CoV-2 after the Omicron BA.1 wave. However, the published studies examining the general population or specific groups, e.g., blood donors or children, uniformly showed a high increase in infection-induced antibodies [ 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 ]. The wide spread of infections and gradual rise in vaccination coverage in the period covered in this study, although at a slower pace than in 2021, resulted in a high proportion of people with positive SARS-CoV-2 antibodies.…”
Section: Discussionmentioning
confidence: 99%
“…Serial cross-sectional studies in British Columbia revealed that infection-induced seroprevalence was less than 15% in early autumn 2021 but increased across Omicron waves to 61% [ 41 ]. Despite high vaccination coverage, the emergence of Omicron had an immense impact on infection-related seroprevalence [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…From May 2020 (continuing until March 2023), Canadian Blood Ser vices, in partnership with the COVID19 Immunity Task Force, tested samples from all Canadian provinces (not Quebec and the territories) for SARSCoV2 antibodies. 2,3 Monthly reports were openly and routinely distributed to provincial and national pub lic health professionals, posted on the COVID19 Immunity Task Force website (https://www.covid19immunitytaskforce.ca /seroprevalenceincanada) and used to estimate the population prevalence of SARSCoV2 in mathematical models.…”
mentioning
confidence: 99%
“…We believe that blood donor serosurveillance can provide timely, geographically broad, regular measurement of nucleocapsid and spike antibodies. 3 An ideal detection system for emerging pathogens would link health administra tion data (e.g., vaccine history and results of molecular testing). Canadian Blood Ser vices is undertaking a pilot study to link SARSCoV2 seroprevalence data to admin istrative data from at least 1 province.…”
mentioning
confidence: 99%
“…However, the different studies presented in this Special Issue support the maintenance of R&D activities by blood operators, who are most qualified to define the specific needs in terms of blood safety and the most efficient technical developments required to meet these needs. In addition, blood transfusion services play an important, but often underappreciated, role in general public health, as illustrated by the experience of the Canadian Blood Services reported by Drews, O’Brien, and their colleagues [ 11 , 12 ]. Blood services’ involvement in public health includes support for the surveillance of emerging viral infections beyond blood-borne viruses (i.e., SARS-CoV2) using the blood donor population as a sentinel group (O’Brien et al [ 12 ]), together with the detection and rapid treatment of unsuspected viral infections (van den Berg et al [ 13 ]) and the characterization and development of new therapeutics (Lachert et al [ 14 ]).…”
mentioning
confidence: 99%